Effect of Suspension Massage Exercise Technique on Core Muscle Mass and Postural Control Ability of Patients with Stroke - SUN Jie; CHEN Guijuan; XU Han; ZHANG Tianyu; DING Yi; WANG Shurui; LI Li (康复学报)
ObjectiveTo investigate effect of suspension massage exercise technique on core muscle mass and posture control ability of patients with stroke.MethodsA total of 58 patients with postural control disorders after stroke who met the inclusion and exclusion criteria were recruited and randomly divided into control group and experiment group, with 29 patients in each group. In the end, 27 cases were included in the control group and 29 cases in the experiment group. The control group received conventional rehabilitation treatment, while the experiment group received suspension massage exercise techniques in addition to the treatment received in the control group. Before and four weeks after treatment, patients were evaluated with the Postural assessment scale for stroke patients (PASS), the Berg balance scale (BBS), the Fugl-Meyer assessment lower extremity (FMA-LE), and the modified Barthel index (MBI). Surface electromyography (sEMG) was used to measure the median frequency (MF) and integrated electromyography (iEMG) of the patients' bilateral erector spinae and multifissure muscles.ResultsBefore treatment, there was no statistically significant difference in PASS, BBS, FMA-LE, MBI scores, or bilateral erector spinae and multifidus MF and iEMG values between the two groups (P>0.05). After treatment, both groups showed higher scores of PASS, BBS, FMA-LE, and MBI, as well as MF and iEMG values of the affected erector spinae and multifidus muscles, and MF values of the healthy erector spinae and multifidus muscles in the experiment group were higher than those before treatment in the same group (all P<0.05). There were statistically significant differences in PASS, BBS, FMA-LE, and MBI scores (P<0.05), MF and iEMG values of the affected erector spinae and multifidus muscles (P<0.05), and MF values of the healthy erector spinae and multifidus muscles (P<0.05) between the two groups. Correlation analysis revealed that the PASS score was positively correlated with the MF value of the affected erector spinae muscle (r=0.404, P=0.030), and the PASS score was positively correlated with the MF value and iEMG value of the affected multifidus muscle (r=0.443, P=0.016; r=0.412, P=0.026), The PASS score was positively correlated with the MF value and iEMG value of the healthy multifidus muscle (r=0.728, P=0.000; r=0.407, P=0.028), and the postural transformation dimension score was positively correlated with the MF value of the healthy multifidus muscle and iEMG value of the affected multifidus muscle (r=0.609, P=0.000; r=0.381, P=0.042).ConclusionThe suspension massage exercise technique is effective for postural control disorders after stroke, improve the contraction efficiency and posture control ability of trunk core muscles, and reduce muscle fatigue, which is recommended for clinical application .